Sistema de seguimento solar de um eixo com diferentes estratégias de seguimento para módulos fotovoltaicos - Rocha Filho, José Itanor do Couto (2016)
This document presents the development of a solar tracking system of one axis to a photovoltaic module (PV) in the city of Fortaleza/CE, with components and strategies targeting to obtain a reduced consumption of electricity. For module positioning, three sun tracking strategies were used. In the first, the module movement is made of pre-defined form, defining the times that the module position is updated and the value of the increase in its angular position at each positioning. In the second, a mathematical algorithm was used to make the calculation of the position of the sun in every moment during the day, and the module positioning was made in accordance with the obtained solar angles. In the third, light sensors were used in the module to make detection of the position of the sun in relation to the module and keep it aligned with the sun during the day. Through experiments, were obtained and analyzed gains in power generation provided by the tracking module with each of the strategies used in different climatic conditions, in relation to a fixed PV module. The strategy that made the sun tracking with more accuracy and provide the highest daily liquid gains was that based on the solar algorithm, with values between 127.98 Wh (52.71%) and 38.55 Wh (22.08%), being obtained in the weighted average a value of 48.87%. With the strategy using the light sensors the gains were similar, with a value of 47.15% in the weighted average. With pre-defined tracking, with less accuracy, there was a reduction in gain, with a maximum value of 96.60 Wh (41.05%) in a day of clear sky. By varying the intervals of time between each module positioning, allowing the module to present higher angular deviation from the sun, it was found that for deviations below to 1° the drop in energy gain was reduced, with higher values for deviations bigger than 3.7°. The high rates of daily solar irradiation, with an average value of 5.45 kWh/m2 during the days of experiments, in the city of Fortaleza, latitude -3.74°, contributed to obtain considerable values of gains. The electricity consumption by the tracking system was reduced, with a maximum value of 4.274 Wh/day for the strategy with predefined tracking and minimum of 2.495 Wh/day for the strategy with the solar algorithm. The significant gains, even with strategies with smaller precision on the tracking of the Sun, shows the potential for the use of solar tracking in photovoltaic modules in Fortaleza.